Bas Jan Ader’s Ludic Conceptualism: Performing a transnational identity - Schoenberger, Janna (Farol, 2021)
Following Huizinga’s ideas in his Homo Ludens (1938), I propose the term Ludic Conceptualism to describe the art that flourished in the Netherlands from 1959 to 1975. Unlike the more severe strands of conceptualism developed in New York and the United Kingdom, play was central to its Dutch incarnation. In this chapter I will show how Dutch conceptual artist Bas Jan Ader’s fixation on his identity, as staged through satirical jokes based on national stereotypes, is key in understanding his art. While a great deal of the humor is obvious in Ader’s work, there has been no serious inquiry into his comedic practice. I will position Ader within the framework of post-war humorous conceptual art prevalente both in the Netherlands and California, locales in which Ader had lived and studied. Using theories of humor and identity I will demonstrate how Ader’s jokes are closely tied to social contexts on both sides of the Atlantic, environments relevant to the artist’s development in the course of his short career. A close examination of Ader’s work will reveal that the artist’s blurred identity as seen in his use of humor is, in fact, a central feature of his art.